Matrix-weighted consensus with leader-following topologies - Trinh, M.H.; Ye, Mengbin; Ahn, H.S.; Anderson, B.D.O. (2017)
In this paper, we report some results on a matrix-weight consensus algorithm. Specifically, the leader-following graph is studied in detail. We study conditions for reaching a consensus in two types of leader-following graphs using the matrix-weighted consensus algorithm. The results will be used to interpret several social behaviors. Simulation results are also provided to vindicate the mathematical analysis.